Up-to-dateness of management by objectives - Cempírek Václav; Drahotský Ivo; Vrbová Petra (Melandrium, 2015)
Management by objectives known as MBO is one of the tools used for control of managers and completion of company results. The MBO in general is considered as a tool for setting up targets and particular control of large companies. The main aim of this work is to discuss the up-to-datedness and usability of Management by Objectives in this turbulent time. The main goal of this paper is to prove, that the MBO is not up-to-date in this time by a particular example - by a simulation of Cost-saving measure of within a manufacturing international company in which determining the specific objectives of a particular worker might bring the company higher additional costs even when seemingly fulfilled individual goals. The results of the simulation are evaluated in the context of theoretical foundations and other similar studies. On the basis of these results, there is provided a set of recommendations for the particular company. This paper is based mainly on the research of Czech and foreign literature, observation in the company for 2 years, interviews with managers and analysing internal documents of the company.
Aktuální řízení podle cílů
Keywords: management by objectives; simulation; cost-saving measure; additional costs; řízení podle cílů; simulace; úsporná opatření; dodatečné náklady